Trade facilitation provisions in regional trade agreements traits and trends - Nora Neufeld (World Trade Organization (WTO), 2014)
The paper first surveys the Trade Facilitation landscape at the regional level and analyses the main forces shaping it. It identifies key factors driving regional Facilitation approaches, examining their priorities, features and underlying philosophies. The study also highlights significant trends in regional Trade Facilitation provisions and analyses their implications. The paper then compares regional and multilateral initiatives, looking at areas of convergence and divergence, and highlighting where potential gaps exist. It analyses negotiating positions in the respective frameworks and discusses both the benefits and limitations of the resulting Trade Facilitation provisions. Examining the impact of the recently concluded WTO Agreement, the study highlights its potential value added.
Keywords: F13; F15; F53; 330; regional trade agreements; trade facilitation; WTO Agreement on Trade Facilitation